Afghan children and adolescents: The burden of poor mental health in contexts of widespread poverty, social inequality and persistent violence. (May 2022) - Nascimento, Renato Bruno Holanda; de Matos Brasil, Aloisio Gomes; Pires, Jeully Pereira; de Moura Gabriel, Italo Wanderson; Bezerra, Bruno Lívio Luna; Bessa, Maria Misrelma Moura; Neto, Modesto Leite Rolim; Lima, Nadia Nara Rolim; Gurgel e Silva, Sergio Quezado; de Alcântara, Thales Bezerra
Abstract: In Afghanistan, the burden of poor mental health arises in contexts of widespread poverty, social inequality, and persistent violence. Generations of Afghans were born during the conflict, and some never knew peace. Children make up more than half (57%) of the population in need of emergency humanitarian assistance in Afghanistan. Recent assessments indicate that more than a third of children have been exposed to psychological distress due to the loss of family and community members and the constant risk of death and injury. Children and teens are struggling with anxieties and fears, desperately in need of mental health support. The lack of social support manifested itself in various forms of suffering in both children and adolescents. The quality of the environment where children and adolescents grow up shapes their well-being and development. Highlights: In Afghanistan, the burden of poor mental health arises in contexts of widespread poverty. Generations of Afghans were born during the conflict, and some never knew peace. Children represent more than half (57%) of the population in need of emergency humanitarian assistance in Afghanistan.